2001
DOI: 10.1104/pp.125.2.573
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of an Arabidopsis Patatin-Like Gene, STURDY, by Activation T-DNA Tagging

Abstract: Activation T-DNA tagging can generate dominant gain-of-function mutants by overexpression of a particular endogenous gene. We identified an activation-tagged mutant, sturdy, exhibiting a stiff inflorescence stem, thicker leaves, shorter siliques, larger seeds, round-shaped flowers, and delayed growth. It is most important that unlike its wild-type counterpart, this mutant is less prone to lodging. Cloning of STURDY revealed that in sturdy, there is an open reading frame containing a single intron encoding a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 44 publications
(34 reference statements)
2
46
0
1
Order By: Relevance
“…In contrast with groups 1 and 2 pPLAs, little is known about the involvement of pPLAIIIs in plant processes. During a screen for lodging resistant plants, an activation-tagged mutant of pPLAIIId, designated STURDY, was isolated; it displayed a stiff inflorescence stalk, thick leaves, and large seeds (Huang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with groups 1 and 2 pPLAs, little is known about the involvement of pPLAIIIs in plant processes. During a screen for lodging resistant plants, an activation-tagged mutant of pPLAIIId, designated STURDY, was isolated; it displayed a stiff inflorescence stalk, thick leaves, and large seeds (Huang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…We have used "activation tagging" in tomato to facilitate the rapid functional analysis of genes involved in metabolic pathways. Activation tagging produces dominant mutations by means of the overexpression of endogenous genes with transcriptional enhancers that cause the ectopic expression of genes in the vicinity of the T-DNA insertion site (Borevitz et al, 2000;Van der Fits and Memelink, 2000;Weigel et al, 2000;Huang et al, 2001;Zubuko et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mis-regulation of four patatin (pat)-like genes of tobacco [24,25] did not become obvious in our S-and VSplants. STOREKEEPER is known to bind to promoters of pat-like genes [5] and over-expression of pat-like genes lead to increased sturdiness in Arabidopsis [3]. We found that the ectopic expression of stk01 and stk03 did not result in aberrant phenotypes in transgenic Arabidopsis (data not shown).…”
Section: Leaves To Inflorescencementioning
confidence: 52%
“…Therefore, a favourable trait is an increased sturdiness of the crop, i.e. an enlarged or more robust stem in relation to plant height [3]. In the last century, plant breeding efforts to generate sturdier crops that are also able to carry heavier fruit loads were mainly generated by introgression of dwarf mutations into commercial varieties, e.g.…”
Section: Introductionmentioning
confidence: 99%